Political Economy in Macroeconomics - Drazen, Allan (Princeton University Press, 2018)
Originally, economics was called political economy, and those studying it readily accepted that economic decisions are made in a political world. But economics eventually separated itself from politics to pursue rigorous methods of analyzing individual behavior and markets. Recently, an increasing number of economists have turned their attention to the old question of how politics shape economic outcomes. To date, however, this growing literature has lacked a cogent organization and a unified approach. Here, in the first full-length examination of how political forces affect economic policy decisions, Allan Drazen provides a systematic treatment, organizing the increasingly influential "new political economy" as a more established field at the highly productive intersection of economics and political science. Although he provides an extraordinarily helpful guide to the recent explosion of papers on political economy in macroeconomics, Drazen moves far beyond survey, giving definition and structure to the field. He proposes that conflict or heterogeneity of interests should be the field's essential organizing principle, because political questions arise only when people disagree over which economic policies should be enacted or how economic costs and benefits should be distributed. Further, he illustrates how heterogeneity of interests is crucial in every part of political economy. Drazen's approach allows innovative treatment--using rigorous economic models--of public goods and finance, economic growth, the open economy, economic transition, political business cycles, and all of the traditional topics of macroeconomics. This major text will have an enormous impact on students and professionals in political science as well as economics, redefining how decision makers on several continents think about the full range of macroeconomic issues and informing the approaches of the next generation of economists
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Nov 2018)
Keywords: Decision making; Economics; Macroeconomics; Policy sciences; Wirtschaftspolitik; Makroökonomie; Politische Ökonomie